Putative Biomarkers in Tears for Diabetic Retinopathy Diagnosis - Amorim, Madania; Martins, Beatriz; Caramelo, Francisco; Gonçalves, Conceição; Trindade, Grimalde; Simão, Jorge; Barreto, Patrícia; Marques, Inês; Leal, Ermelindo Carreira; Carvalho, Eugénia; Reis, Flávio; Ribeiro-Rodrigues, Teresa; et al. (Frontiers in Medicine, 2022)
Purpose: Tear-fluid biomarkers may offer a non-invasive strategy for detecting diabetic patients with increased risk of developing diabetic retinopathy (DR) or increased disease progression, thus helping both improving diagnostic accuracy and understanding the pathophysiology of the disease. Here, we assessed the tear fluid of nondiabetic individuals, diabetic patients with no DR, and diabetic patients with nonproliferative DR (NPDR) or with proliferative DR (PDR) to find putative biomarkers for the diagnosis and staging of DR. Methods: Tear fluid samples were collected using Schirmer test strips from a cohort with 12 controls and 54 Type 2 Diabetes (T2D) patients, and then analyzed using mass spectrometry (MS)-based shotgun proteomics and bead-based multiplex assay. Tear fluid-derived exosomes were analyzed by transmission electron microscopy, Western Blotting, and nano tracking. Results: Proteomics analysis revealed that among the 682 reliably quantified proteins in tear fluid, 42 and 26 were differentially expressed in NPDR and PDR, respectively, comparing to the control group. By multicomparison analyses, we also found significant changes in 32 proteins. Gene ontology (GO) annotations showed that most of these proteins are associated with oxidative stress and exosomes. Indeed, we also found that tear fluid is particularly enriched in exosomes. T2D patients with NPDR have higher IL-2/-5/-18, TNF, MMP-2/-3/-9 concentrations than the controls. In the PDR group, IL-5/-18 and MMP-3/-9 concentrations were significantly higher, whereas IL-13 was lower, compared to the controls. Conclusions: Overall, the results show alterations in tear fluid proteins profile in diabetic patients with retinopathy. Promising candidate biomarkers identified need to be validated in a large sample cohort.